2005
DOI: 10.1016/j.jmatprotec.2005.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Development of a non-intrusive heat transfer coefficient gauge and its application to high pressure die casting

Abstract: This paper presents a design for a robust sensor suitable for determining heat flow and heat transfer coefficient in high pressure die casting. A design methodology for the sensor is presented, together with the conclusions of this analysis. A sensor has been manufactured to these principles and some typical results from its operation are introduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 14 publications
5
51
0
2
Order By: Relevance
“…The HTC can have a large influence on the response time. Having an unsheathed TC the situation can be compared with high pressure die casting where HTC of 10000 Wm -2 K -1 may be found [11]. Having a ceramic-sheathed TC the HTC will probably only be 500 Wm -2 K -1 or even less.…”
Section: Response Timementioning
confidence: 99%
“…The HTC can have a large influence on the response time. Having an unsheathed TC the situation can be compared with high pressure die casting where HTC of 10000 Wm -2 K -1 may be found [11]. Having a ceramic-sheathed TC the HTC will probably only be 500 Wm -2 K -1 or even less.…”
Section: Response Timementioning
confidence: 99%
“…At the beginning, the molten metal flowed into the sprue at a speed of 50 m•s , which is the highest among all of TnFs. According to Dour et al [16] , a higher velocity always leads to a higher heat flux. This trend was also observed by Guo et al [20] and Hamasaiid et al [8] .…”
Section: φ60mentioning
confidence: 98%
“…Guo et al pointed out that the influence of the pressure would only be prominent if the casting step is sufficiently thick for a step-shape casting [15] . Dour et al reported that a higher velocity always leads to a higher heat transfer coefficient and heat flux [16] . Furthermore, Papai, et al found that the peak value of heat flux or heat transfer coefficient decreases as the initial die temperature increases [17] .…”
mentioning
confidence: 99%
“…> Pour le moulage sous pression, la pression d'intensification appliquée a peu d'effet sur le transfert de chaleur alors que la vitesse du piston a un effet significatif [10,41]. La vitesse du piston aurait une influence plus marquée comparativement à la pression d'intensification [10].…”
Section: Avantagesunclassified
“…Il est bien connu que la pression influence le transfert de chaleur à l'interface de deux médias et que cet effet sature au-delà d'une certaine valeur de pression [41].…”
Section: Avantagesunclassified